EVALUATION OF THE ANTIDIABETIC EFFECT OF OCIMUM SANCTUM IN TYPE 2 DIABETIC PATIENTS: Pharmaceutical Science-Pharmacology - G. SOMASUNDARAM; K. MANIMEKALAI; SALWE, KARTIK J.; J. PANDIAMUNIAN (International Journal of Life Science and Pharma Research, 2012)
This study was carried out to find out the antidiabetic effect of Ocimum Sanctum (O. sanctum) in type 2 diabetes patients as so many studies have showed its antidiabetic effect experimentally but very few studies are performed to investigate the efficacy in humans. The study was performed in two different groups for a period of 90 days. One group received Glibenclamide and other one received Glibenclamide plus O. sanctum. Fasting blood glucose (FBG) and Post prandial Blood Glucose level (PPBG) were estimated at the time of enrolment in the study and then after 30 days and 90 days. The group which received Glibenclamide, showed a significant drop in the mean FBS as well as PPBS. Fasting Blood glucose level was 174.35 gm/dl on day 1, which dropped significantly to 114.50 gm/dl on 90th day. Post prandial blood glucose levels was 247.31 gm/dl, on day 1, which dropped significantly to 152.02 gm/dl on 90th day. The group which received Glibenclamide plus O. sanctum also showed a significant drop in the FBS as well as PPBS level. Fasting blood glucose level on day 1 was 171.53 gm/dl, which dropped significantly to 103.50 gm/dl on day 90 and post prandial blood glucose was 254.13 gm/dl on day 1, which dropped significantly to 143.12 gm/dl on day 90. The drop in both FBG and PPBG levels was more in the group which received Glibenclamide plus O. sanctum. The group which received Glibenclamide, showed a significant drop in the Glycosylated Haemoglobin (HBA1c) levels when compared between day 1 to day 90. The group which received Glibenclamide plus O. sanctum also showed a significant drop in the Glycosylated Haemoglobin (HBA1c) level when compared between day 1 to day 90. The drop in HBA1c levels was more in the group which received Glibenclamide plus O. sanctum. All of the patients were observed for hypoglycaemic episodes at every visit from Day 1 to Day 90. More than 80% of the subjects who received only Glibenclamide and Glibenclamide plus O. sanctum did not have any hypoglycaemic episodes. Thus from the results we can conclude that Ocimum sanctum can be used as an adjuvant in Type 2 Diabetes Mellitus patients.